LA DIGITALIZACIÓN DE LA RADIO DEPORTIVA - Hilario José ROMERO BEJARANO (Fonseca, Journal of Communication, 2023)
Radio has been immersed in recent years in a phase of technological integration and business of multimedia, as well as diversification of systems and channels for broadcasting. In addition, Internet has been consolidated as the platform of digital radio that more has evolved as a result of its continued expansion. However, the merger radio-Internet must be understood as a new form of communication, and not solely as a new complementary medium.